2008
DOI: 10.1038/sj.bjc.6604759
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between effects on time-to-disease progression and overall survival in studies of metastatic breast cancer

Abstract: The relationship between overall survival (OS) and disease progression end points has been demonstrated in colorectal, colon, and non-small cell lung cancers. We assessed the association between OS and time-to-progression (TTP) or progression-free survival (PFS) in metastatic breast cancer (MBC) studies. A literature search retrieved all randomised controlled trials since 1994 in patients with MBC in which OS and either TTP or PFS were reported. Summary data on trial and patient characteristics were abstracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 14 publications
(18 reference statements)
2
55
0
3
Order By: Relevance
“…This issue is even more complicated in international clinical trials when the clinical practice of secondline therapy varies as widely as is seen in advanced gastric cancer. The use of surrogate endpoints, including PFS or time to tumor progression, to evaluate the efficacy of firstline treatment has been extensively studied in trials of colorectal and breast cancers, and data from many metaanalyses indicate that PFS is a good endpoint to evaluate the efficacy of first-line chemotherapy [56][57][58]. Standardization of evaluation of tumor progression is needed to validate the usefulness of these surrogate endpoints in trials of systemic therapy for gastric cancer [59].…”
Section: Discussionmentioning
confidence: 99%
“…This issue is even more complicated in international clinical trials when the clinical practice of secondline therapy varies as widely as is seen in advanced gastric cancer. The use of surrogate endpoints, including PFS or time to tumor progression, to evaluate the efficacy of firstline treatment has been extensively studied in trials of colorectal and breast cancers, and data from many metaanalyses indicate that PFS is a good endpoint to evaluate the efficacy of first-line chemotherapy [56][57][58]. Standardization of evaluation of tumor progression is needed to validate the usefulness of these surrogate endpoints in trials of systemic therapy for gastric cancer [59].…”
Section: Discussionmentioning
confidence: 99%
“…Results from numerous analyses in a variety of solid tumours demonstrate that the effects of treatment on pfs are strongly associated with the effects of treatment on os 44 . Similar analyses have demonstrated that, among patients with metastatic breast or colorectal cancer, gains in time to disease progression are generally associated with no gains or with very slight gains or losses in pps 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a review of randomized control trials from 2004 to 2009 on breast, colorectal, and non-small cell lung cancer, Booth and Eisenhauer found a 26% increase in the use of PFS as a primary endpoint [19]. In contrast, breast cancer researchers showed that the prediction of OS based on PFS is uncertain [20,21]. Although we found an increased use of PFS as primary endpoint over time, this was not correlated with an increase in FDA approval rate.…”
Section: Discussionmentioning
confidence: 99%